1994
DOI: 10.1080/0260747940200306
|View full text |Cite
|
Sign up to set email alerts
|

The Management of the Induction of Newly Qualified Teachers in Primary Schools

Abstract: This study is based on two years of empirical work with new teachers employed in the primary schools of five local education authorities (LEAs) in England. Interviews with all those with a stake in the management of probation and induction of newly qualified teachers in primary schools were analysed in terms of patterns and dilemmas to create a proposal for effective induction support and probation management. The article examines the role of LEAs and schools in structured induction. Case studies of pairs of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…It is therefore surprising to find that the current induction framework and the accompanying guidelines do not contain any reference to the pastoral dimension. Studies conducted by Turner (1994) and Tauer (1998) confirmed that where pastoral support was strong, newly qualified teachers flourished in terms of professional and personal growth. Where it was lacking, confidence and performance were affected.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…It is therefore surprising to find that the current induction framework and the accompanying guidelines do not contain any reference to the pastoral dimension. Studies conducted by Turner (1994) and Tauer (1998) confirmed that where pastoral support was strong, newly qualified teachers flourished in terms of professional and personal growth. Where it was lacking, confidence and performance were affected.…”
Section: Discussionsupporting
confidence: 64%
“…As is evident from the literature, a great number of research studies have been conducted on the subject of induction, based on an immense diversity of settings (Olson & Osborne, 1991;Kyriacou, 1993;Waterhouse, 1993;Calvert & Henderson, 1994;Turner, 1994;Bolam et al, 1995;Gibson, 1995;Menter, 1995;Leahey, 1997;Blake & Hanley, 1998;Bleach, 1998Bleach, , 1999Capel, 1998;Brading, 1999;Barrington, 2000;Tickle, 1994Tickle, , 2000. Within each setting, the various aspects of induction were examined in relation to the professional and personal development of newly qualified teachers.…”
Section: Introductionmentioning
confidence: 97%
“…Within such a traditional conceptualisation of professionalism novice teachers run the risk of being denied the entitlement to continued support and guidance, least of all pastoral. And yet, Turner (1994) and Tauer (1998) consider this dimension as essential in a mentor development programme. Their study provides evidence in support of the claim that where pastoral support was strong, newly qualified teachers flourished in terms of professional and personal growth.…”
Section: Presentation Of the Resultsmentioning
confidence: 96%
“…It must incorporate the humanistic, person-centred aspects of mentoring (Turner, 1994;Tauer, 1998;Jones, 2000;Tickle, 2000), within which learning is embedded within social activity via a collaborative, multi-support system (Fabian & Simpson, 2002), and transcend the boundaries of the conventional, dyadic mentoring relationship. Furthermore, it must comprise a community of 'critical friends' representing a diverse range of professional experience and expertise at various levels of seniority and include multi-cultural perspectives of professional learning.…”
Section: Reflections and Conclusionmentioning
confidence: 99%
“…In common with other research findings from England, general support and encouragement are emphasised by the first-year teachers rather than mentors' professional skills -such as acquaintance with the school curriculum and educational theories or their ability in dealing with administrative workwhich are regarded as relatively less important (Boydell & Bines, 1994). Thus, forming a good relationship with probationers personally and professionally is an essential task for mentors (Wubbles et al, 1987;Turner, 1994). Such emphases resonate also with Yang et al's (1991) findings in Taiwan.…”
Section: Expectations Of the Role Of Mentor In Taiwanmentioning
confidence: 99%